Learning Connected Speech by Pronouncing Song Lyrics: Students' Perspective - Auliatuz Zahrotul Jannah; Sulton Dedi Wijaya; Ro'ifah Ro'ifah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
Connected speech is a big role in English and has to be understood and mastered by English learners. 20 English Education Department students which are included in the English learner category are the subject of this research. This study aims to investigate how students’ perspective on learning connected speech by pronouncing song lyrics. This study used a qualitative method to focus on analyzing students’ thoughts and it presented descriptively. To collect the data, the researcher used questionnaires and interviews. Totally 58 statements in questionnaires and 16 questions through interviews have given to the subject as a completion. The main finding of this research is all subject loved to listening English song. They has positive responses on learning connected speech using song lyrics. They state that learning connected speech by pronouncing song lyrics can be an effective and fun way. They also feel confident, happy, and close to natives. By seeing the finding, it can be conclude that the problem that existed like students' difficulty when listening to the native speaker speaking, bad pronunciation, shame, less fluency, and even no connected speech are tackled. Moreover, they can learn without boredom because they learn in the way they loved.